Периодическая система химических элементов Д. И. Менделеева - Пикуль О. В. (Логосвос, 2019)
Экземпляры: БС (20190826) / Инвентарный номер: РГП311 / Цена: / Сис.шифр: 24 / Авт.знак: П 27 / ГРНТИ: 31 / ББК: 24я72